Exploiting the Layout Engine to Assess Diagram Completions - Mazanek, Steffen; Maier, Sonja; Minas, Mark (Electronic Communications of the EASST, 2008)
A practicable approach to diagram completion is to first compute model completions on the abstract syntax level. These can be translated to corresponding diagram changes by the layout engine afterwards. Normally, several different model completions are possible though. One way to deal with this issue is to let the user choose among them explicitly, which is already helpful. However, such a choice step is a quite time-consuming interruption of the editing process. We argue that users often are mainly interested in completions that preserve their original diagram as far as possible. This criterion cannot be checked on the abstract syntax level though. In fact, minimal model changes might still result in enormous changes of the original diagram. Therefore, we suggest to use the layout engine in advance for assessing all possible model completions with respect to the diagram changes they eventually cause.